Design and Evaluation of a “Gamified” System for Improving Career Knowledge in Computing Sciences - Scholtz, Brenda; Raga, Larissa; Baxter, Gavin (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2016)
“Gamification”, or the use of game elements outside the gaming context, is a recent trend in learning approaches and has been used to digitally engage and motivate people to accomplish their learning objectives. The study described in this article investigated components of a gamification system and the impact of these components on user experience, usability and education usability. The Mechanics, Dynamics and Aesthetics (MDA) classification framework for gamification design was used to guide the authors’ design of a gamification system intended to improve learners’ knowledge of careers in computing sciences (CS). Criteria for evaluating e-learning systems were derived from literature and used to extend the MDA framework via addition of criteria for evaluating usability, user experience (UX) and educational usability of a gamification system. The extended MDA framework was found to be successful in guiding the design, development and evaluation of the system prototype, and the results gathered from the summative usability evaluation indicated that positive UX and educational usability were achieved. The results suggest that gamification designed for UX and educational usability can potentially play an important role in equipping young people in South Africa with a knowledge of CS-related careers.
Keywords: computing sciences (CS); gamification; Mechanics, Dynamics and Aesthetics (MDA) classification framework; usability; user experience (UX); educational usability